Lake Baikal amphipods and their genomes, great and small - P. B. Drozdova; E. V. Madyarova; A. N. Gurkov; A. E. Saranchina; E. V. Romanova; J. V. Petunina; T. E. Peretolchina; D. Y. Sherbakov; M. A. Timofeyev (Вавиловский журнал генетики и селекции, 2024)
Endemic amphipods (Crustacea: Amphipoda) of Lake Baikal represent an outstanding example of large species flocks occupying a wide range of ecological niches and originating from a handful of ancestor species. Their development took place at a restricted territory and is thus open for comprehensive research. Such examples provide unique opportunities for studying behavioral, anatomic, or physiological adaptations in multiple combinations of environmental conditions and thus attract considerable attention. The existing taxonomies of this group list over 350 species and subspecies, which, according to the molecular phylogenetic studies of marker genes, full transcriptomes and mitochondrial genomes, originated from at least two introductions into the lake. The studies of allozymes and marker genes have revealed a significant cryptic diversity in Baikal amphipods, as well as a large variance in genetic diversity within some morphological species. Crossing experiments conducted so far for two morphological species suggest that the differences in the mitochondrial marker (cytochrome c oxidase subunit I gene) can potentially be applied for making predictions about reproductive isolation. For about onetenth of the Baikal amphipod species, nuclear genome sizes and chromosome numbers are known. While genome sizes vary within one order of magnitude, the karyotypes are relatively stable (2n = 52 for most species studied). Moreover, analysis of the diversity of repeated sequences in nuclear genomes showed significant betweenspecies differences.  Studies of mitochondrial genomes revealed some unusual features, such as variation in length and gene order, as well as duplications of tRNA genes, some of which also underwent remolding (change in anticodon specificity due to point mutations). The next important steps should be (i) the assembly of whole genomes for different species of Baikal amphipods, which is at the moment hampered by complicated genome structures with high repeat content, and (ii) updating species taxonomy taking into account all the data.